Edukasi Peran Zat Besi pada Pencegahan Anemia di SMP Negeri 06 Ketapang - Dwisari, Fath; Dermawan, Abdurraafi' Maududi; Amalia, Puspa; Azmi, Khulul; Ramadhani, Natasya Intan; Purwanti, Desi Asih (Lembaga Pengembangan Kinerja Dosen, 2025)
Anemia is a common health problem among adolescents, often caused by iron deficiency. This educational activity aimed to improve students' knowledge about the role of iron in preventing anemia. The program was conducted at SMP Negeri 06 Ketapang and involved 35 students as respondents. The results showed that after the educational session, the majority of students were in the moderate knowledge category (19 students or 54.3%), followed by the high category (7 students or 20%) and the low category (9 students or 25.7%). It can be concluded that this educational activity was quite beneficial in increasing students’ knowledge about the importance of iron in anemia prevention.